USING sma-its2 PRIMER FOR ITS2 (Internal Transcribed Spacer-2)-BASED MOLECULAR CHARACTERIZATION OF Anopheles minimus FROM KULONPROGO, YOGYAKARTA - INDONESIA - Kartika Senjarini; Berlian Permata Dewi Erlambang; Naura Paramitha Cindy Ardyah; Devi Astikaningrum; Rike Oktarianti; Syubbanul Wathon (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
Malaria is a public health threat caused by the Plasmodium infection transmitted by the Anopheles mosquito. Malaria vector control is highly dependent on the ability to determine mosquito species' vectorial and bionomic capacity. Species identification based on morphological characteristics as well as DNA-barcoding approaches is a very important step in determining vectorial capacity. Our research group has redesigned a new ITS2 primer, namely, sma-its2, which is specifically able to identify the Anopheles (An.) mosquito vector but cannot identify other mosquito vectors. This study wanted to test this primer's specificity further for identification of other Anopheles mosquitoes. We used An. minimus collected from Kulonprogo, Yogyakarta – Indonesia. The methods used in this research are as follows: landing collection, morphological identification, isolation of genomic DNA, PCR (Polymerase Chain Reaction), PCR product purification, sequencing, and data analysis. An. vagus from Bangsring, Banyuwangi – Indonesia, which had previously been identified using the same primary, was used as a positive control. The results of the morphological analysis showed that both species were in accordance with the vector identification key used in this study. The molecular analysis showed that the sma-its2 primer could amplify the ITS2 sequence of An. vagus and An. minimus, producing 650 – 700 bp. However, further analysis of the ITS2 sequences of both species, resulted in the same species, namely An. vagus, with a different accession number in GenBank. This showed that the sma-its2 primar can be used to identify An. vagus but cannot be used to identify An. minimus. Analysis of the primer position in the ITS2 sequences showed the presence of 3 nucleotides in the forward sma-its2 primer that was not recognized by the An. minimus sequences and thus, hinder the successful identification of these species.